Addams Family values [videorecording (Blu-Ray)] - Rudnick, Paul; Huston, Anjelica; Julia, Raul; Lloyd, Christopher, 1938-; Cusack, Joan, 1962-; Kane, Carol, 1952-; Ricci, Christina (Paramount, 2019)
It's love at first fright when Gomez and Morticia welcome a new addition to the Addams household, Pubert, their soft, cuddly, mustachioed baby boy. As Fester falls hard for voluptuous nanny Debbie Jilinksy, Wednesday and Pugsley discover she's a black-widow murderess who plans to add Fester to her collection of dead husbands. The family's future grows even bleaker when the no-good nanny marries Fester and has the kids shipped off to summer camp.